Penerapan Model Pembelajaran Problem Based Learning (PBL) Melalui Pendekatan Teaching at the Right Level (TaRL) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VII - Ica Endang Lestari; Swasti Maharani; Sri Sunarni (Departement of Mathematics Education, 2024)
Teaching at the Right Level (TaRL) is a learning approach that does not focus on class level but rather focuses on the level of cognitive ability of each student in the class. This approach provides students with the opportunity to learn according to their cognitive abilities. Meanwhile, Problem Based Learning (PBL) is a learning model that provides problems in real life with the aim that students are expected to be able to build their own knowledge and understanding of the material they study. The aim of this research is to improve student learning outcomes in class VII-E of SMP Negeri 11 Madiun through the application of the Problem Based Learning (PBL) learning model using the Teaching at the Right Level (TaRL) approach. This research was conducted in 2 cycles on March 7 2024 and March 28 2024 using Classroom Action Research (PTK) with research subjects of 28 class VII-E students at SMP Negeri 11 Madiun for the 2024/2025 academic year. The research process was carried out by implementing learning in groups according to the level of students' cognitive abilities and given problems through LKPD. One class is divided into 7 groups according to the results of the diagnostic assessment that have been analyzed. Groups 1, 2 and 3 consist of students who have low ability to solve problems independently who are then given guidance and scaffolding, groups 4 and 5 have moderate ability to solve problems independently and are given a little scaffolding. Meanwhile, groups 5 and 6 have high abilities in solving problems independently. The data collection instrument used in this research is student learning outcomes (Summative Assessment). From the initial test results, it was found that only 8 students' learning outcomes data met the KKM with a percentage of students' learning completion of 28.57%. In cycle I, the learning outcomes of students who met the KKM increased to 16 students with a percentage of student learning completion of 57.14%. Then in cycle II there was an increase again, where the learning outcomes of students who met the KKM became 23 students with a percentage of student learning completion of 82.14%, while the other 5 learning outcomes did not meet the KKM. Thus it can be concluded that the application of the Problem Based Learning (PBL) learning model with the Teaching at the Right Level (TaRL) approach can improve student learning outcomes.